Giovani e materia : ricerca e tendenza. - Spadolini, Benedetta; Sogese; Gambone, Bruno ([s.l.] : Sogese, 1993)
57a Mostra Mercato Internazionale dell' Artigianato
Adlib record nr. 530010948
boek
Keywords: Italië